Challenges in developing a split drive targeting dsx for the genetic control of the invasive malaria vector Anopheles stephensi - Mireia Larrosa‐Godall; Joshua X. D. Ang; Philip T. Leftwich; Estela González; Lewis Shackleford; Katherine Nevard; Rob Noad; Michelle A. E. Anderson; Luke Alphey (2025)
Abstract Background Anopheles stephensi is a competent malaria vector mainly present in southern Asia and the Arabian Peninsula. Since 2012, it has invaded several countries of eastern Africa, creating an emerging risk of urban transmission. Urgent efforts are required to develop novel and more efficient strategies for targeted vector control. CRISPR/Cas9-based homing gene drives have been proposed as attractive alternative strategies. Gene drives have the potential to spread a desired trait through a population at higher rates than via normal Mendelian inheritance, even in the presence of a fitness cost. Several target genes have been suggested and tested in different mosquito vector species such as Anopheles gambiae and Aedes aegypti . Several promising suppression drives have been developed in An. gambiae that target the sex determination gene doublesex ( dsx ). Methods In this study, a geographically confineable gene drive system targeting dsx was developed ( dsx gRNA ). Here, a transgenic line which expresses Cas9 under the control of the endogenous zpg promoter was generated. Separately a transgenic line which expresses a gRNA targeting the female specific exon of dsx was inserted into that same target site. The reproductive fitness of males and females heterozygous and homozygous for this element was determined. A series of experimental crosses was performed to combine the two elements and assess the homing rate of the dsx element in a split drive system. Results The drive was able to home in a super-Mendelian rate comparable to those obtained by an autonomous drive in this species. Although inheritance rates as high as 99.8% were observed, potentially providing very potent gene drive, dominant effects on male and female fertility were observed, which would be sufficient to hinder spread of such a drive. Molecular analysis indicated that the gRNA expressing insertion disrupted normal splicing of dsx . Conclusions These results should be considered when proposing the viability of dsx as a target gene for a population suppression gene drives in Anopheles stephensi . Although high homing rates were observed, the fitness defects found in both males and females carrying the transgene would likely prohibit this drive from functioning in the field. Graphical Abstract